Disparities in socio-economic drivers behind China's provincial energy-related mercury emission changes. (1st December 2019) - Guo, Yaqin; Zhang, Bonan; Chen, Bin; Yang, Qing; Li, Jiashuo
Abstract: The legally binding Minamata Convention was ratified by the Chinese government in 2017, implying that mercury emission mitigation policy design has become an urgent task ever since. As each provincial region has different energy structures and technology levels, their mercury emission profiles may have heterogeneity, thus requiring targeted regional control polices. Therefore, this study investigates the provincial energy-related mercury emissions and identifies their underlying socioeconomic factors during 2007–2012, by combining structural decomposition analysis (SDA) with the multi-regional input-output analysis (MRIO). Results show that the rising consumption per capita and decreasing emission factor are the largest contributors to emission growth and decline, respectively. However, their contributions vary significantly across regions. The rising consumption per capita leads to nearly 20 t emission increase in Shandong and Jiangsu, but less than 1 t in Qinghai. The decreasing emission factor's negative effect on mercury emission reduction is extremely important in Jiangsu, Shandong and Guangdong, but not so obvious in most western provinces. Energy efficiency is another critical contributor to mercury reduction in all provinces except Guizhou, as the coal consumption in Guizhou nearly doubled during 2007–2010. Moreover, production structure and consumption structure have opposite effects during 2007–2010 and 2010–2012: they first drive energy-related mercury emissions growing in most provinces, then inhibit the emissions especially in Shandong and Guangdong. These findings point to targeted mercury mitigation strategies (for example: improving energy efficiency in Guizhou and Liaoning, optimizing economic structure in Henan and Sichuan) for each province. Highlights: MRIO-SDA is conducted to identify driving factors of mercury emissions. Driving factors' effects vary significantly across provincial regions. Consumption structure's effects are opposite during 2007–2010 and 2010–2012. Emission factor is the largest contributor to the decline. Targeted provincial mercury mitigation strategies are comprehensively discussed.